Where is the EC drifting? - Hans Möller (Intereconomics, 1980)
The squabbles in the European Community have made the headlines in the last few months. Wide-spread is the impression that the EC is laboriously threading its way from compromise to compromise without evolving proper longer-lasting solutions for its problems. The community is adrift. Where will the drift take it? Prof. Möller advances a medium-term projection. Prof. Hrbek follows it up with a presentation of this thesis that to view the EC as an artefact drifting erratically without purpose, direction or orientation gives a wrong picture of the Community.
Keywords: 330; European Communities